(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s ((3eMeO Hf CHj WGdH GdHOQi s)
(3ChdgG (B:s
(3CNHGQ hVGM hfSHg hVGM dbH ZdH Ydjg dLeGdg hHgGFg s
(3BNQgG (B:s
(3UhJ HGf GdNdjW hdh WhYJ eG HGfG hbWYhG ef LHGd GdhUd GbQGfG hPcQ GHf Gdeci Cfg deYHO gPG BNQ GdLRA GdSGOS s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(8627) s
Keywords: (3GdCOHs